Exploring the interaction effects of board meetings on information disclosure and financial performance in public listed companies - Noor Azuddin Jakob; Norraidah Abu Hasan (Economies, 2021)
The board of directors' role is paramount in businesses because it reflects the organisation's ability to earn investor confidence and improve financial performance. This paper aims to examine the relationship between environmental and social (ES) information disclosure and firm financial performance and the interaction effects of board meetings on the relationship between ES and firm performance in Malaysian publicly traded firms from 2013 to 2017. This article contributes to the theoretical foundations of the agency theory as it relates to the corporate governance function. The agency theory framework is used to capture the inherent interrelationships between the board of directors and firm performance. The study's findings indicate that a firm's relationship between ES and financial performance, measured by Tobin Q and return on equity, may be significantly affected by board meetings.
Keywords: 330; financial performance; agency theory; board meeting; environmental and social disclosure; GMM